THE MAIN CHARACTERS DEPRESSION IN JASMINE WARGAS MY HEART AND OTHER BLACK HOLES - Euis Desiyana Fitri; Ni Made Widisanti; Maulana Taufik (Journal Albion : Journal of English Literature, Language, and Culture, 2022)
The topic of this research is the depression experienced by the main character in the Jasmine Wargas My Heart and Other Black Holes with the formulation problem on how the form of depression in the main character is and the efforts made by the main character to overcome the depression that she is going through. This research uses the descriptive analysis method with data analysis techniques in the form of a literature study using the perspective of literary psychology and a psychological review of depression and intrinsic elements such as character and characterization, plot, conflict, and settings. The results of this study are that the main character experiences a major depression with various physical, psychological, social symptoms, emotional and motivational symptoms, and some triggering factors that are psychological factors with several self-defense mechanisms and the main character's efforts in overcoming her depression.Keywords: Depression; Main Character; Self-defense Mechanism; Overcome Depression.